Evaluation the biological effect of niosomal hydrogel base amphotericin in combination with Artemisia sieberi essential oil for treatment of cutaneous leishmaniasis: In vitro and in vivo studies - Hanieh Ardeshiri; Amir Hossein Radfar; Gholamreza Hatam; Mohammad Saleh Bahreini; Negar Azarpira; Shreeshivadasan Chelliapan; Hesam Kamyab; Seyed Reza Kasaee; Ali Mohammad Amani; Sareh Mosleh-Shirazi (Results in Chemistry)
Leishmania is an obligate intracellular parasite that is endemic in many countries. It has two main subtypes of cutaneous leishmaniasis (CL) and visceral leishmaniasis (VL). The cutaneous type is non-fatal, but immediate treatment is essential to prevent annoying cosmetic outcomes and financial burdens for patients. The current treatments for cutaneous leishmaniasis (CL) are expensive, with many side effects and indeterminate outcomes. The aim of this study was to investigate the potential of Amphotericin B (AmB) niosomal hydrogel, alone and in combination with Artemisia sieberi essential oil (ASEO), as a treatment for cutaneous leishmaniasis. Niosomes were prepared by the thin-film hydration method. The results showed that the average size of AmB, ASEO, and AmB + ASEO niosomes were 80, 92, and 104 nm, respectively. The results revealed the excellent amount of drug loading for these products. In vitro studies indicated that the lethal effects of AmB, ASEO, and AmB + ASEO were 87.14, 85.31 and 89.73 %, respectively. MTT assay was applied to evaluate the cytotoxicity of various concentrations of products. The in vivo results on BALB/c mice revealed a significant reduction in lesion size in the AmB hydrogel niosomal and AmB + ASEO hydrogel niosomal. In conclusion, the results suggest that hydrogel niosomal AmB and AmB + ASEO could be considered as the novel and effective treatments for CL.